Clinical and immunological characteristics of type 1 diabetes mellitus in a northwestern Colombian population (2006)
We underwent a project aimed to define the clinical and immunological characteristics of type 1 diabetes (T1D) in a Colombian population. This was a multicenter and cross-sectional study. Patients were systematically interviewed and their medical records reviewed, using a questionnaire that sought information about demographic, clinical and immunological characteristics. Glutamic acid decarboxylase antibodies (GADA), tyrosine phosphatase antibodies (IA-2A) and insulin antibodies (IAA) were examined by radioimmunoassay. There were 107 patients with T1D. Male:female ratio was 1:1. Half of the patients developed diabetes ketoacidosis at onset. GADA, IA-2A, and IAA were detected in 45%, 40%, and 69% of the cases, respectively. GADA positive patients were older and had a less duration of disease than patients without these autoantibodies (p less than 0.01). Association between breast feeding with the presence of antibodies or clinical characteristics was not observed. The results highlight some differences of T1D expression according to geographic location and ethnicity. Differences in age at onset and clinical variables may point to an environmental factor or deficient access to health care system. Genetic studies underway will provide important information in this population. These results might help to define public health policies in our population to improve T1D diagnosis, patients' quality of life and their outcome. © 2005 Elsevier Ireland Ltd. All rights reserved.